From Fields to Microclimate: Assessing the Influence of Agricultural Landscape Structure on Vegetation Cover and Local Climate in Central Europe - Jan Kuntzman; Jakub Brom (Remote Sensing)
Agricultural intensification through simplification and specialization has homogenized diverse landscapes, reducing their heterogeneity and complexity. While the negative impact of large, simplified fields on biodiversity has been well-documented, the role of landscape structure in mitigating climatic extremes and stabilizing climate is becoming increasingly important. Despite considerable knowledge of landscape cover types, understanding of how landscape structure influences climatic characteristics remains limited. To explore this further, we studied an area along the Czech–Austrian border, where socio-political factors have created stark contrasts in landscape structure, despite a similar topography. Using Land Parcel Information System (LPIS) data, we analyzed the landscape structure on both sides and processed eight Landsat 8 and 9 OLI/TIRS scenes from the 2022 vegetation season to calculate spectral indices (NDVI, NDMI) and microclimatic features (surface temperature, albedo, and energy fluxes). Our findings revealed significant differences between the two regions. Czech fields, with their larger, simpler structure and lower edge density, can amplify local climatic extremes. In contrast, the distribution of values on the Austrian side was more even, likely due to the greater diversity of cultivated crops, a more spatially diverse landscape, and a balanced spread of agricultural activities over time. In light of climate change and biodiversity conservation, these results emphasize the need to protect and restore landscape complexity to enhance resilience and environmental stability.